Validation of synthetic M-protein materials for external quality assessment: homogeneity, commutability, and stability - Moniek M. Bioch; Theo Rispens; Corrie M. de Kat Angelino; Anke J. ten Haaken-Meijer; Miranda van Berkel; Marc H.M. Thelen; Joannes F.M. Jacobs (Clinical Chemistry and Laboratory Medicine (CCLM), 2026)
Abstract Objectives Accurate quantification of M-proteins is important for clinical management of monoclonal gammopathies. Reliable assessment of trueness on M-protein quantification in External Quality Assessment (EQA) schemes is difficult due to the lack of reference methods and materials for target value assignment. We propose a strategy to produce targeted synthetic M-protein EQA materials by spiking known amounts of human(ised) therapeutic monoclonal antibodies (t-mAb) into null serum. This paper validates homogeneity, commutability, and stability of these materials. Methods Homogeneity was assessed on two aliquoted synthetic M-protein EQA materials comparing within-vial variation with between-vial variation for sodium, total protein, IgG and M-protein quantification. Commutability was assessed by comparing between-method differences in 51 patient-derived and nine synthetic M-protein EQA materials among various M-protein quantification methods. Stability was checked by reanalysis of two previously distributed synthetic M-protein EQA materials. Results Within- and between-vial variation were similar in both samples, and therefore homogeneity criteria were met. Commutability was observed for eight out of nine samples, whereas one hypergammaglobulinemic sample was non-commutable. Long-term storage stability at −80 °C was found acceptable in both samples. Conclusions Due to their proven homogeneity, commutability, and stability, targeted synthetic M-protein EQA materials are suitable for use in M-protein EQA schemes. This allows for the assessment of laboratory performances based on target values, and opens the way for harmonisation and exchangeability of M-protein diagnostic methods. Additionally, it provides a new source for the production of M-protein EQA materials, alleviating the demand for large volumes of patient material needed to organise M-protein EQA schemes.